House of Lords: voting, peers' attitudes and perceptions of legitimacy, 2000-2007 - Russell, Meg (UK Data Service, 2012)
This project investigated changes in behaviour and attitudes following the reform in 1999 which removed the majority of hereditary peers from the House of Lords. The central research question was whether the (still unelected) second chamber would grow in confidence and strength as a result of its least defensible element being removed, and the resultant change in party balance which saw it become a 'no overall control' chamber. Through study of peers' voting records, and particularly of government defeats in the chamber, the project assessed the impact of the second chamber on policy. It also investigated changing behaviour within the party and Crossbench groups. Sources included the public record, particularly Hansard, postal questionnaire surveys of peers conducted in 2005 and 2007, in-depth interviews with peers and public opinion poll questions on the MORI Omnibus surveys fielded in 2005 and 2007. Users should note that this study includes only the data from the 2005 survey of peers, the 2005 public opinion poll, defeats and divisions from 2000-2006 and publicly-available demographic information on peers.